Gratitude, Spirituality, and Life Satisfaction of Pakistani and Malaysian University Students: A Cross-Cultural Study - Meddour, Houcine; P., Nur Khairunniza S. (International Review of Management and Marketing, 2025)
The aim of this research was to investigate the gratitude, spirituality, and life satisfaction of Pakistani and Malaysian university students. The research design of this study was correlational. The total sample (N =470) were collected form Pakistani and Malaysian universities through purposive sampling. Both men and women regular university students with age range of 20 to 35 years were included in this research. The data were collected using Gratitude Questionnaire, Satisfaction with Life and The Centrality of Religiosity Scale. The results were calculated through SPSS (24.0). The results from correlation found gratitude has significant positive relationship with life satisfaction and spirituality. While life satisfaction has a significant and positive relationship with spirituality. The results also found that gratitude, spirituality, age and education are significant predictors in life satisfaction. The gender differences found significant higher the mean score of gratitude, life satisfaction and spirituality among female students than male students. In cultural differences, the gratitude, life satisfaction, and spirituality have significantly higher among Pakistani university students as compared with Malaysian university students. While gratitude, spirituality and life satisfaction are higher among Muslim university students as compared with non-Muslim university students. This research will be helpful for psychologist, researcher, teachers, university students and government agencies of Pakistani and Malaysian for policymaking.